2018
DOI: 10.1139/cjpp-2017-0307
|View full text |Cite
|
Sign up to set email alerts
|

Syk inhibitor R406 downregulates inflammation in an in vitro model ofPseudomonas aeruginosainfection

Abstract: As Pseudomonas aeruginosa infections are characterized by strong inflammation of infected tissues, anti-inflammatory therapies in combination with antibiotics have been considered for the treatment of associated diseases. Syk tyrosine kinase is an important regulator of inflammatory responses, and its specific inhibition was explored as a therapeutic option in several inflammatory conditions; however, this has not been studied in bacterial infections. We used a model of in vitro infection of human monocytic ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…Although the underlying molecular mechanisms are still being defined, SYK is known to regulate ROS production and lysosomal activity, 2 significant signals for NLRP3 inflammasome activation in macrophages [24]. It was recently found that inhibition of SYK reduced the release of bioactive IL-1β by macrophage cells infected by P. aeruginosa [31]. This suggests that SYK may regulate innate immune responses to P. aeruginosa via its involvement in inflammasome activation.…”
Section: Effect Of Syk Inhibitor In P Aeruginosa Infectionmentioning
confidence: 98%
See 4 more Smart Citations
“…Although the underlying molecular mechanisms are still being defined, SYK is known to regulate ROS production and lysosomal activity, 2 significant signals for NLRP3 inflammasome activation in macrophages [24]. It was recently found that inhibition of SYK reduced the release of bioactive IL-1β by macrophage cells infected by P. aeruginosa [31]. This suggests that SYK may regulate innate immune responses to P. aeruginosa via its involvement in inflammasome activation.…”
Section: Effect Of Syk Inhibitor In P Aeruginosa Infectionmentioning
confidence: 98%
“…For this reason, many pharmaceutical companies and academic institutions have been involved in the development of small molecule SYK inhibitors. Recent studies have demonstrated the ability of SYK to regulate the production of proinflammatory molecules by bronchial epithelial and monocytic cells, which are stimulated with TNF-α, rhinovirus, or P. aeruginosa [25,27,30,31,41]. For these reasons, SYK may represent an attractive target for a new therapeutic strategy of treating P. aeruginosa infection by inhibiting SYK kinase.…”
Section: Syk and Innate Immunitymentioning
confidence: 99%
See 3 more Smart Citations